The analysis of groundwater table variations in Termez district of Surkhandarya region, Uzbekistan: A spatio-temporal approach - Arifjanov Aybek; Samiyev Luqmon; Eshboyev Navruz; Xodjimuxamedova Shaxida; Akramov Jamoliddin; Makhmudov Bekzod (BIO Web of Conferences)
The trend analysis of the study was acquired by selecting multiyear seasonal groundwater table data and monitors the wells in each sub-area under the study area. To calculate and assess the spatial differences in the inanition of groundwater table, geostatistical methods was applied based on data from 14 groundwater wells during the period from January 2000 to December 2021 which were obtained from a secondary source, “Uzbekhydrogeology” State Institution. The geographic information system was used to assess the spatial change in order to find the level of groundwater. In this study, Inverse Distance Weightage was applied for estimating the attribute values of locations that are within the database using known data values. Then the interpolated data values were extracted for Statistical Analysis using Man-Kendall’s Test. Finally, based on the results of the Mann-Kendall test (Z) and Sen's Slope (Q), seasonal changes of the groundwater level were determined, and electronic maps of the area were created using the IDW interpolation method.